2021
DOI: 10.3389/fpsyt.2021.632496
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Health, Sleep Quality, Behavior, and Internet Use Among People During the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Background: The COVID-19 pandemic has led to an increase in the risk of suicide, uncertainty, mental stress, terror, annoyance, weariness, financial issues, and frustration. We aim to determine the prevalence of insomnia, depressive and anxiety symptoms, and their associated factors among Libyan populations during the COVID-19 pandemic and the civil war.Methods: An online cross-sectional survey was conducted among the Libyan population between July 18 and August 23, 2020. The data collected included basic demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 64 publications
0
45
1
2
Order By: Relevance
“…While staying at home, they need to identify and plan focused, beneficial activites that can enhance their positive emotions. Education could also help individuals creatively optimize limited house space to engage in physical activities that promote incidental and intentional physical exercise, and reduce the risks of obesity ( 19 , 20 ). School administrations should also support health education via practical, creative and targeted videos to help increase awareness about healthy eating, nutrition, sleep and other aspects of behavioral health ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…While staying at home, they need to identify and plan focused, beneficial activites that can enhance their positive emotions. Education could also help individuals creatively optimize limited house space to engage in physical activities that promote incidental and intentional physical exercise, and reduce the risks of obesity ( 19 , 20 ). School administrations should also support health education via practical, creative and targeted videos to help increase awareness about healthy eating, nutrition, sleep and other aspects of behavioral health ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the depression prevalence was 3-fold higher during the COVID-19 outbreak than before [41], 32.7% of adults from the Chinese general population experienced elevated anxiety or depressive symptoms [42]. Moreover, nearly half of the Libyan population suffered from depressive symptoms, and one-fifth presented severe anxiety symptoms [43,44]. Univariate logistic regression showed that depression and anxiety were associated with younger age and female gender, while multivariate logistic regression indicated that only female gender remained significant.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that the likelihood of having depression and/or anxiety was higher in participants reporting mental and/or physical fatigue. Indeed, fatigue and depression share specific symptoms such as sleep disturbances, poor concentration, and memory difficulties [43,61]. This explains why patients with either fatigue or depression are reported to be two-fold prone to show an increased risk for the comorbid presentation of both traits, compared to the general population [62].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dickerson & Kemeny (2004) conducted a meta-analysis of the relationship between the characteristics of stressors and cortisol responses, and found that tasks containing uncontrollable elements were associated with robust cortisol reactivity [42]. It is possible that in a situation where action is restricted worldwide, the physical symptoms of stress response, such as exhaustion, or changes in sleeping habits [43] are also seen, which may have led to an increase in parenting stress. However, there are some individual differences in tolerance to stressors.…”
Section: Discussionmentioning
confidence: 99%